Systemic inflammation, microbiology, and clinical outcomes in eosinophilic and non-eosinophilic acute exacerbations of chronic obstructive pulmonary disease - Ning Zhang; Qiqiang Zhou; Sujie Zhao; Chen Zhang; Yahong Chen; Ying Liang; Yongchang Sun (Frontiers in Medicine, 2026)
Objective Blood eosinophil (EOS) guides corticosteroid therapy in stable chronic obstructive pulmonary disease (COPD), but its prognostic value in COPD exacerbation (ECOPD) remains controversial. This study characterized clinical features and assessed the impact of EOS levels on clinical outcomes in hospitalized ECOPD patients. Methods We retrospectively reviewed hospitalized patients with ECOPD between 2018 and 2023. Patients were categorized according to percentage of peripheral blood eosinophil: the eosinophilic group (EOS ≥ 2%) and the non-EOS group (EOS < 2%). The primary outcome was in-hospital mortality, while the secondary outcomes included ICU admission, mechanical ventilation, and length of hospital stay. Results Among 511 patients (EOS group, n = 139; non-EOS group, n = 372), the EOS group had lower levels of inflammatory markers (C-reactive protein and procalcitonin) and a lower detection rate of Gram-negative bacilli, especially Acinetobacter baumannii . The EOS group exhibited significantly lower rates of ICU admission (25.18% vs. 50.27%; P < 0.001) and in-hospital mortality (1.44% vs. 6.72%; p = 0.018). In the multivariable analyses, EOS% ≥ 2% remained associated with lower odds of in-hospital mortality after adjustment for age and heart failure (adjusted OR, 0.225; 95% CI, 0.052–0.971; p = 0.046) and with lower odds of ICU admission after adjustment for age, sex, and heart failure (adjusted OR, 0.357; 95% CI, 0.229–0.556; p < 0.001). Conclusion Among hospitalized patients with ECOPD, elevated peripheral blood eosinophils were associated with favorable clinical outcomes, especially a reduced risk of ICU admission, as well as a lower systemic inflammation burden.